Uterine carcinosarcoma: a rare and aggressive neoplasm - Agrawal, Trupti; Satia, Meena; Badhwar, Vijaya; Bandhu, Rishita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine carcinosarcoma (UCS) is a rare highly aggressive tumor accounting for 2-3% of all uterine malignancies. It’s characterized by postmenopausal bleeding and often presents with a palpable pelvic mass. The tumors usually contain both malignant epithelial carcinomatous and sarcomatous mesenchymal components. Herewith presenting a case report of a patient with postmenopausal bleeding with a 16 weeks size lump in the abdomen.